Assessing levels of support provided to home visitors in the US during the COVID-19 pandemic. (2nd October 2022) - Crouch, Elizabeth; Radcliff, Elizabeth; Browder, Jennifer; Workman, Lauren; McClam, Maria
Abstract : During the global COVID-19 pandemic, home visiting programmes became increasingly important. The purpose of this study was to investigate levels of support provided to individual home visitors in South Carolina, US, by their lead implementing agencies, using a telephone survey. The results showed that two thirds of sites reported difficulties during the pandemic, and site leads had to be creative in providing support to their staff. It is concluded that strong, functional home visiting programmes can play a crucial role in assuring the wellbeing of vulnerable families. Therefore, levels of support for home visitors are vital, especially during a public health crisis.